Integration of Cognitive, Affective, and Psychomotor Domain Scoring in Islamic Religious Education - Pranajaya, Syatria Adymas; Idris, Jamaluddin; Abidin, Zainal; Mahdi (Sinergi International Journal of Education, 2023)
An educator must consider the levels in each domain (cognitive, affective and psychomotor) when compiling scores and weighting questions. This is also the case in Islamic Religious Education lessons. The purpose of writing this article is to explain the integration of scoring for cognitive, affective, and psychomotor domains along with examples in Islamic religious education questions. Using literature studies, there are conclusions obtained from this article, namely the benefits for students, 1). Helps students to develop balanced competencies. 2). Helps students to understand the relationship between knowledge, attitudes, and skills. 3). Helps students to become a whole person with integrity. So it is highly recommended for educators to be able to carry out the right application, with the integration of cognitive, affective, and psychomotor domain scoring in order to become one of the important instruments to improve the quality of Islamic religious education in the world of education.